IMPLEMENTASI AKAD IJARAH DALAM PEMANFAATAN LAPANGAN OLAHRAGA DITINJAU DARI PRINSIP MUAMALAH (STUDI KASUS DI STADION PALAGAN AGUNG MA’HAD AL-ZAYTUN) - Rahmatan Lil Alamin, Panji; Aminulloh, Ali; Maulana, Rizal (Cahaya Ilmu Bangsa, 2024)
Ijarah is a form of muamalah that contains elements of mutual assistance, where not all individuals are able to have the facilities needed to support sports activities, so they choose to rent. The Palagan Agung Stadium, which is located in the Ma’had Al-Zaytun environment, is one of the infrastructure facilities owned by YPI Ma’had Al-Zaytun, and its management rights have been given to KOSMAZ. This facility plays a very important role in supporting sports activities for the Ma’had Al-Zaytun community. The purpose of this study is to determine the implementation of the ijarah contract in the utilization of sports fields at the Palagan Agung Ma’had Al-Zaytun Stadium and to determine the review of muamalah principles in the ijarah contract for the utilization of sports fields at the Palagan Agung Ma’had Al-Zaytun Stadium. The method used in this study is a qualitative approach with the type of field research. Data collection techniques include observation, interviews with YPI Ma’had Al- Zaytun, KOSMAZ and tenants (OPMAZ and IKAMAZ) and are equipped with documentation. The results of the study show, first: The implementation of the ijarah contract in the utilization of the sports field at the Palagan Agung Stadium involves two parties, namely the first party is YPI Ma’had Al-Zaytun as the lessor, who grants the right to manage the Palagan Agung field to KOSMAZ, and the second party is IKAMAZ and OPMAZ as the lessor. The process begins with communication between the lessee and the manager of the Palagan Agung Stadium, namely KOSMAZ, to find out the rental provisions, including the time and date of use, wages or rental fees, and payment procedures. These provisions are conveyed verbally by KOSMAZ. After the lessee agrees to the provisions, payment is made through the YPI Ma’had Al-Zaytun finances, considering that the Palagan Agung Stadium facilities belong to YPI Ma’had Al- Zaytun which are managed by KOSMAZ. Proof of payment in the form of a receipt is then submitted to KOSMAZ, after which the lessee can use the Palagan Agung Stadium facilities. Second: The principle of muamalah in the ijarah contract for the utilization of the sports field at the Palagan Agung Stadium can be concluded that this process is in accordance with the principles of muamalah. The lease transaction is carried out on the basis of an agreement and voluntarily between the two parties without any element of coercion, in this case stated in the rental process where the lessee is aware of the rental provisions for the Palagan Agung Stadium which have been set by YPI Ma’had Al-Zaytun and KOSMAZ. Keywords: Ijarah Contract, Utilization of Sports Fields, Muamalah Principles